IMMU-42. ADOPTIVE HEMATOPOIETIC STEM CELL AND APD1 THERAPY CONVERGE IN THE THYMUS TO PROMOTE ANTI-GLIOBLASTOMA IMMUNITY. (14th November 2022) - Francis, Connor; Font, Laura Falceto; Figg, John; Dean, Bayli DiVita; Sebastian, Mathew; Jin, Dan; Long-James, Kaytora; Von Roemeling, Christina; Reid, Alexandra; Moore, Ginger; Mitchell, Duane; Flores, Catherine
Abstract: Our lab previously published that adoptive hematopoietic stem cell (HSC) therapy administered in conjunction with aPD1 increases median survival in multiple models of CNS malignancies. Tumor-infiltrating lymphocytes (TIL) abundance is independently associated with better outcomes in many cancers. Impressively, approximately 25% of TILs are HSC-derived in early disease. Importantly, we show HSC therapy generates de novo TILs in a thymus-dependent fashion and offer evidence of altered central tolerance following aPD1 therapy, which may permit immune activation against a larger pool of tumor-associated antigens. Therapeutic HSCs were prepared from constitutive GFP-expressing (CD45.2 + ) and PD1 KO (CD45.2 + ) mice and transferred into CD45.1 + hosts. Sublethal 5Gy total body irradiation was administered day 5 post-intracranial tumor implantation. The next day, 1E6 HSCs from a 1:1 – GFP:PD1 KO cocktail were injected intravenously. Descriptive statistics are reported as mean ± SD. Transferred HSCs engraft, expand, differentiate, and migrate to form approximately 25% of the TIL compartment in only 15 days. We found that, 56.2% ± 20.3 of CD3 + TILs display a thymocyte-like CD4 + CD8 + (DP) phenotype in early disease, and 43.8% ± 17.4 of these DP-TILs are HSC-derived. Interestingly, DP-TILs were virtually absent in advanced disease 29 days after treatment. At this stage, HSC-derived TILs most commonly fell within the single-positive (SP) TIL subsets, comprising 9.8% ± 5.6 of SP-CD8 + TILs. Notably, HSC PD1KO -derived cells were 4x more abundant amongst SP-CD8 TILs when compared to HSC GFP -derived cells (6.5% vs 1.6%, p < 0.05). SP-CD8 thymocytes were similarly enriched for HSC PD1KO progeny (41.1% vs 24.7%, p < 0.05) which may suggest PD-1 blockade directly promotes thymopoiesis. The privileged maturation of PD1-deficient HSCs is intriguingly reversed when GFP:PD1 KO HSCs are co-transferred into non-tumor-bearing mice. Thus, we show the thymus is an active site where PD-1-blocking agents function, and that HSC + aPD1 therapy is uniquely positioned to leverage thymus-dependent anti-tumor immunity.